SOCIOECONOMIC INEQUALITIES, WATER, SANITATION, HYGIENE AND DIARRHEAL DISEASE AMONG CHILDREN UNDER FIVE YEARS IN INDONESIA - Erni Astutik; Tika Dwi Tama (Universitas Airlangga, 2024)
Background: Diarrheal diseases are still a serious digestive tract infection in Indonesia. The geographical areas with lower socioeconomic inequalities and water, sanitation and hygiene (WASH) contribute to incline diarrheal disease among children under 5 years old. Purpose: This study aimed to map the distribution of diarrheal diseases among children under 5 years old and identify areas with higher risk in socioeconomic status and WASH. Methods: This study used secondary spatial data repository from Indonesia Demographic Health Survey 2017. This study used ecological approach to provide visual geographic distribution of diarrheal diseases among children under 5 years old, as well as to identify the risk based on the socioeconomic inequalities and WASH. The map production was performed by GIS software. Results: We found that provinces with higher percentage of diarrheal diseases in children also had higher percentage of population with the lowest socioeconomic status. Additionally, the provinces which had higher unimproved drinking water sources, unimproved sanitation facility, and limited handwashing facility, had the higher percentage of diarrheal disease among children under 5 years. Conclusion: The percentage of the lowest socioeconomic status and unimproved WASH might contribute to incline the percentage of diarrheal disease among children under 5 years. The government needs to consider the geographical area to decrease the diarrheal diseases among children under 5 years.